Cancer Bioinformatics 2006
DOI: 10.1002/0470032898.ch4
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Models of Cancer

Abstract: Modelling and simulation are indispensable for the study of biological systems as dynamical ensembles, made up of a large number of interacting components and exhibiting complex non-linear behaviour. These methods provide the tools for data and knowledge-based in silico predictions of tumour behaviour and hypothesis formulation in both preclinical and clinical settings (see also Chapter 1 and later chapters in this section).The number of mathematical models that describe solid tumour dynamics has increased dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
(133 reference statements)
0
1
0
Order By: Relevance
“…In 1984, a mathematical model for the growth of breast cancer was proposed (Botesteanu, Lipkowitz, Lee & Levy, 2016), and it was found that different individual tumors grew according to Gompertz parameters. With this basic growth model, it was possible to estimate that a cancerous cell would take eight years to be detected, referring to the fact that a tumor is a group of cells that grow without control and its growth is limited to the space and resources available (Patel & Nagl, 2006), which makes it more complicated to describe its growth and behavior as opposed to growth under an exponential model. Hence, from that day forward, the use of the Gompertz model has been widely used in cancer research.…”
Section: And Biosciencesmentioning
confidence: 99%
“…In 1984, a mathematical model for the growth of breast cancer was proposed (Botesteanu, Lipkowitz, Lee & Levy, 2016), and it was found that different individual tumors grew according to Gompertz parameters. With this basic growth model, it was possible to estimate that a cancerous cell would take eight years to be detected, referring to the fact that a tumor is a group of cells that grow without control and its growth is limited to the space and resources available (Patel & Nagl, 2006), which makes it more complicated to describe its growth and behavior as opposed to growth under an exponential model. Hence, from that day forward, the use of the Gompertz model has been widely used in cancer research.…”
Section: And Biosciencesmentioning
confidence: 99%